2018
DOI: 10.1055/s-0038-1676090
|View full text |Cite
|
Sign up to set email alerts
|

Fibromyalgia and Irritable Bowel Syndrome in Female Pelvic Pain

Abstract: Fibromyalgia and irritable bowel syndrome are common disorders which often coexist in women with chronic pelvic pain. Like pelvic pain, these disorders describe symptoms without pathologic findings. Women with chronic pelvic pain have a higher prevalence of fibromyalgia (4–31%) and irritable bowel syndrome (8–41%) than the general population. Aberrant pain processing and psychosocial stressors are implicated in the co-occurrence of these pain syndromes (chronic overlapping pain conditions), but active epidemio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 66 publications
0
13
0
1
Order By: Relevance
“…There is no pathological cause of FMS [ 28 ]. Recent study with functional neuroimaging has consistently demonstrated altered central pain perception in the brain of patients with FMS [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is no pathological cause of FMS [ 28 ]. Recent study with functional neuroimaging has consistently demonstrated altered central pain perception in the brain of patients with FMS [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between gynecological disorders and IBS is well known and has been extensively studied in the literature [16][17][18][19][20], and unjustiied pelvic surgery has even been reported in patients with IBS [21]. A recent primary care registry study on over 13,000 subjects with IBS conirmed a clear association with urogenital symptoms and infections [22].…”
Section: Discussionmentioning
confidence: 99%
“…These diagnoses were chosen because they are common comorbid conditions in women with pelvic floor disorders and are considered by many to represent disorders attributable to central sensitization. 8,[15][16][17][18] Women in the nonpain group were women without any of these conditions. Demographic information collected included age, geographic location, and insurance status (eg, private commercial only, Medicare plus private commercial supplemental).…”
Section: Methodsmentioning
confidence: 99%